Al badar islamic elementary school as representative of leading schools in tulungagung - Anggara Dwinata; Masitah Ahmad; Leny Suryaning Astutik; Noer Af'idah (Yayasan Azhar Amanaa Yogyakarta, 2024)
This research describes the existence of school representation, namely Al Badar Islamic Elementary School as one of the favorite schools in Tulungagung Regency. Favorite schools become reference schools for the community in sending their children to receive quality education. This research uses qualitative research methods with a case study design. The research subjects consisted of the Principal, Teachers and Head of Administration who were the subjects of representation for the school in obtaining valid data. The data collection techniques use observation, documentation and interviews. The results of the research provide an interpretation that Al Badar Islamic Elementary School has become a favorite school in terms of the curriculum implemented which is integrated with the typical curriculum of the school institution, adequate school facilities and infrastructure, competitive graduates, abundant achievements, and adequate human resources. linear and professional. So it can be concluded that Al Badar Islamic Elementary School is present as a high-quality Islamic elementary school in terms of sound and professional institutional management.